Cymbeline - Shakespeare, William, 1564-1616 (Salt Lake City, UT : Project Gutenberg, 1997)
"Cymbeline" by William Shakespeare is a play written around 1611. Set in Ancient Britain, it follows Princess Imogen, who secretly marries Posthumus Leonatus against her father King Cymbeline's wishes. When Posthumus is banished, a cunning Italian lord wagers he can seduce the faithful Imogen. Through deception, disguise, and mistaken identity, the play weaves together themes of innocence and jealousy with kidnapped princes, a scheming queen, political intrigue with Rome, and a series of tragic misunderstandings that threaten to destroy everyone involved. (This is an automatically generated summary.)
The First Folio, 1623
Wikipedia page about this book: https://en.wikipedia.org/wiki/Cymbeline
Release date is 1997-12-01
Keywords: Fathers and daughters -- Drama; Married people -- Drama; Great Britain -- History -- Roman period, 55 B.C.-449 A.D. -- Drama; Britons -- Kings and rulers -- Drama; Tragicomedy